Water Ecosystem Services in Northern Australia—How Much Are They Worth and Who Should Pay for Their Provision? - Zander, Kerstin K. (Public Library of Science, 2013)
There is ongoing pressure to develop the largely unaltered Daly River catchment in northern Australia for agriculture. However, a choice experiment among people in the region and in Australia’s largest city, Sydney, shows that people are prepared to pay substantial amounts to maintain the quality of its ecosystem services. The total stated willingness-to-pay (WTP) for a Daly River conservation programme was about $300, of which people would be willing to pay over half ($161) if the programme retained waterholes for Aboriginal people in good condition. The WTP for high quality recreational fishing and biodiversity values was $120 and $91 respectively. Using the average cost of a recreational fishing license in Australia ($35) as a basis for grounding the stated preferences in empirical values, as well as the cost of park entry fees and the amount of support society provides to agriculture in Australia, the total amount that the 110,000 people in the region are likely to be willing to pay for the retention of the values in the Daly River catchment is about $6 million, while the 4.5 million people in Sydney would be willing to pay about $81 million. A significant finding in this research is that, while fishing, biodiversity and agricultural values all have equivalents in the market economy, the value for which people were willing to pay most, the cultural value, has no equivalent at all and is thus receives almost no investment.